Presiopean / diseinua, Sam Reid ... [et al.] ; itzulpena, José Manuel López Irastorza - Reid, Sam; López Irastorza, José Manuel (; PhET Interactive Simulations, 2011)
Presioa, fluidoak eta dentsitatea lantzeko simulazioa.